Ensino da matemática mediado pelos jogos: interrelações entre o conteúdo ensinado e a aprendizagem desenvolvida por estudantes do ensino fundamental na percepção de professores de matemática - NEVES, Samara Corrêa (2022)
The work aims to address the relationships that arise between the content taught and the learning developed by students in the perception of teachers. This will allow teachers to analyze the students within the school context using the insertion of games in Mathematics classes, thus knowing and being able to improve their abilities. The research was conducted with Mathematics Teachers of the Public Education Network in the municipality of São Domingos do Capim- PA, in order that the games help the mathematical content taught in the classroom, following the new organization of the Common National Curriculum Base - BNCC, where these games are created in order to improve not only the teaching, but also the cognitive behavior and logical thinking of the student. Using the classroom and also outside the school environment as a means of research, raising their mathematical knowledge beyond the school, and establishing an education that is facilitating for children in early grades. However, the games need to be inserted in an effective way, requiring that teachers have a brief knowledge of some practices that Piaget and Vygotsky, and among other theorists establish as being important for the development of the student through this teaching strategy that will be previously inserted. Having as research environment the classroom and its surroundings, the instrument used will be the game, and the research is generated due to the relationships that arise after the content is inserted in the classroom and put into practice.